Between Liberation and Representation: Muslim Women’s Agency and the ‘Savior’ Narrative in Samira Ahmed’s Novels - Ellita Permata Widjayanti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
This article analyzes the representation of Muslim women’s agency in two novels by Samira Ahmed, Love, Hate & Other Filters (2018) and Mad, Bad & Dangerous to Know (2020), using a postcolonial feminist framework, specifically the thought of Mohanty, Spivak, and Abu-Lughod. This research uses textual analysis to identify the character constructions and cultural representations in both novels. The study focuses on three main aspects: (1) agency as a form of self-assertion (liberation as self-assertion), (2) the dynamics of savior narratives that present external savior figures, and (3) tendencies toward re-orientalism. Although Ahmed’s novels attempt to present diasporic Muslim women as independent subjects, these narratives are often trapped within the framework of Western liberal feminism, which defines liberation as a release from cultural and religious values. The presence of external savior figures reinforces savior narratives that position Western validation as a prerequisite for Muslim women’s freedom, while narratives that repeat Western perspectives on the East demonstrate a re-orientalist reproduction.